Human activity’s impact on urban vegetation in China during the COVID-19 lockdown: An atypical anthropogenic disturbance - Yujie Li; Shaodong Huang; Panfei Fang; Yuying Liang; Jia Wang (iScience)
Summary: The COVID-19 lockdown led to reduced industrial and transportation emissions in Chinese cities, improving air quality and affecting large-scale vegetation. This study examines changes in net primary productivity (NPP) across 283 prefecture-level cities in China (PCC) during the lockdown, focusing on aerosol optical depth (AOD), nighttime light (NTL), temperature, and precipitation. Results from spring 2020 show that 53.5% of cities experienced increased NPP, with greater gains in cities with high industrial and traffic activity due to reduced AOD. Structural equation modeling revealed that urban characteristics, particularly industrial levels, influenced NPP primarily through changes in AOD, with human activity shifts playing a larger role than climate factors. In cities with substantial NPP changes, human activity effects were especially pronounced. These findings highlight the complex interactions among urban characteristics, environmental changes, and vegetation responses, offering insights for ecological management and urban planning in the face of future disruptions.